2014
DOI: 10.1002/ejic.201402067
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles Stabilized by Glycodendrimers: Synthesis and Application to the Catalytic Reduction of 4‐Nitrophenol

Abstract: Air-stable gold nanoparticles stabilized by glycodendrimers (AuDSNs) in water were prepared in the presence of a reducing agent, NaBH 4 . A UV/Vis spectroscopy study demonstrates that no spontaneous reduction of Au 3+ ions occurs in the presence of glycodendrimers. The AuDSNs were characterized by UV/Vis spectroscopy and transmission electron microscopy (TEM). TEM images show that the AuDSNs were

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 71 publications
0
15
0
1
Order By: Relevance
“…Metal catalysts could also benefit from the use of polymer dendrimers as stabilization systems. As an example, poly (amidoamine) (PAMAM) and poly (propylene imine) (PPI) dendrimers were applied to stabilize nanoparticles of Au for the reduction of 4NP [119,120]. The results showed that as the dendrimer concentration increased, the rate constants of catalytic reduction for all of the processes studied declined.…”
Section: Photodegradation Of Mb~99%mentioning
confidence: 99%
“…Metal catalysts could also benefit from the use of polymer dendrimers as stabilization systems. As an example, poly (amidoamine) (PAMAM) and poly (propylene imine) (PPI) dendrimers were applied to stabilize nanoparticles of Au for the reduction of 4NP [119,120]. The results showed that as the dendrimer concentration increased, the rate constants of catalytic reduction for all of the processes studied declined.…”
Section: Photodegradation Of Mb~99%mentioning
confidence: 99%
“…These are being designed in order to compose task specific metal nano-catalysts. 1,2,3-Triazolyl click dendrimers containing silicon and external pentose groups (Figure 4a) were conceived in order to secure stoichiometric coordination of Au [74] and Pd [75] ions to the internal triazole groups. This set ratio led to the nucleation of smaller metal cores and larger overall active surfaces that were also able to catalyze Suzuki-Miyaura coupling of 4-bromoacetophenone with phenylboronic acid.…”
Section: The Benchmark Reaction Of P-nitrophenolmentioning
confidence: 99%
“…One of the eicient methods for the removal of nitro compounds is the reduction of them to the corresponding amines, which are versatile precursors in organic synthesis as well as in the preparation of various compounds such as pharmaceuticals and agrochemicals [8][9][10][11]. In recent years, catalytic hydrogenation of nitroaromatic compounds employing different noble transition metals such as Pd [12][13][14] and Au [15][16][17][18][19][20][21][22] was investigated well. Moreover, cheap alternative metals such as Fe [23][24][25][26][27][28][29][30][31][32], Zn [33][34][35][36][37][38], and Sn [39,40] have been widely used for reduction of nitro group.…”
Section: U N C O R R E C T E D P R O O F Introductionmentioning
confidence: 99%